A Comparison of The Recruitment and Selection Process of Virtusa Ltd – Between Two Different Locations - Rajalingam, Vidhushan (2009)
Recruitment and selection practices have become a vital process in today’s business world when the image of an organization is depicted from their employees. Hiring the right candidates at the right time gives an organization a competitive edge to succeed. As the competition in the market is so high having the right kind of recruitment and selection practice in place is important to attract the best talents from the market. However studies have shown varies kind of recruitment and selection practices followed along with the issues faced during the course of hiring the candidates. It also throws a question in the reliability and validity on the selection interview. The purpose of the report is to investigate the recruitment and selection practices followed by a company and compare the practice between two locations. The company chosen for the research is an MNC from the IT sector. This study has some objectives, first to understand the process which is gathered by conducting interviews. Secondly look at the variables making the difference between the two locations. And finally will carry out an empirical analysis based on the collected data from the interviews.